SOCIO-COMMUNICATIVE DEVELOPMENT PROCESSES IN A BILINGUAL ENVIRONMENT (Journal of Universal Science Research, 2026)
This article discusses the role of community in improving social and communicative competence in preschool education through bilingualism, teaching children to communicate in a second language through daily activities and games, as well as the issue of language acquisition in a natural environment through poems, stories, and songs, and the development of childrenʼs problem-solving, collaboration, and creative thinking skills for cognitive and social development